Military Expenditures and Health Outcomes: A Global Perspective - Gillani, Seemab; Shafiq, Muhammad Nouman; Ahmad, Tusawar Iftikhar (iRASD Journal of Economics, 2019)
Health has a major contribution in attaining better human capital and wellbeing both at the individual as well as at country levels. Although military spending may boost economic growth through multiplier and spillover effects, yet tradeoffs exist between military expenditures and health outcomes. Grossman (1972) explains health as output which depends on many input variables. By covering a panel of 156 countries ranging from the time period 1970 to 2014, this study incorporates military expenditures, GDP per capita, urbanization, access to the improved drinking water source, number of physicians, and secondary school enrollment as determinants of health (life expectancy and infant mortality). OLS, fixed effects, random effects, and system GMM have been used as estimation techniques. The study reveals that countries with low military expenditures have a comparatively high life expectancy and low infant mortality as compared to countries with high military expenditures. Robustness of results was checked through sensitivity analyses performed on the bases of determinants of health, international geopolitical scenario, and the development status of the country. The evidence of sensitivity analysis suggests that overall results are robust in life expectancy model but somehow sensitive in case of infant mortality. The study affirms the explicit tradeoff between military expenditures and welfare spending and concludes that hefty defense expenditures lower life expectancy and enhance infant mortality.